Genome wide DNA methylation analysis of Haloferax volcanii H26 and identification of DNA methyltransferase related PD-(D/E)XK nuclease family protein HVO_A0006 - Matthew eOuellette; Laura eJackson; Scott eChimileski; R. Thane ePapke (Frontiers in Microbiology, 2015)
Restriction-modification (RM) systems have evolved to protect the cell from invading DNAs and are composed of two enzymes: a DNA methyltransferase and a restriction endonuclease. Although RM systems are present in both archaeal and bacterial genomes, DNA methylation in archaea has not been well defined. In order to characterize the function of RM systems in archaeal species, we have made use of the model haloarchaeon Haloferax volcanii. A genomic DNA methylation analysis of H. volcanii strain H26 was performed using PacBio single molecule real-time (SMRT) sequencing. This analysis was also performed on a strain of H. volcanii in which an annotated DNA methyltransferase gene HVO_A0006 was deleted from the genome. Sequence analysis of H26 revealed two motifs which are modified in the genome: Cm4TAG and GCAm6BN6VTGC. Analysis of the ∆HVO_A0006 strain indicated that it exhibited reduced adenine methylation compared to the parental strain and altered the detected adenine motif. However, protein domain architecture analysis and amino acid alignments revealed that HVO_A0006 is homologous only to the N-terminal endonuclease region of Type IIG RM proteins and contains a PD-(D/E)XK nuclease motif, suggesting that HVO_A0006 is a PD-(D/E)XK nuclease family protein. Further bioinformatic analysis of the HVO_A0006 gene demonstrating that the gene is rare among the Halobacteria. It is surrounded by two transposition genes suggesting that HVO_A0006 is a fragment of a Type IIG RM gene, which has likely been acquired through gene transfer, and affects restriction-modification activity by interacting with another RM system component(s). Here, we present the first genome-wide characterization of DNA methylation in an archaeal species and examine the function of a DNA methyltransferase related gene HVO_A0006.